The unequal rewards of peer support at work : research shows that men benefit more from supporting colleagues than do women - Baym, Nancy; Hadley, Constance Noonan (MIT Sloan Management Review, 2023)
The authors researched social investments at work and found that women may receive a lower ROI than men do for their work weaving the social fabric of their organizations. Men reported providing less frequent and different types of social support to colleagues than women yet reported higher levels of organizational encouragement and rewards — and job satisfaction. To build future workforce communities both efficiently and equitably, organizations must revisit their policies and e xpectations.